Supplier development and public procurement performance: Does contract management difficulty matter? - Ismail Abdi Changalima; Alban Dismas Mchopa; Ismail Juma Ismail (Cogent Business & Management, 2022)
This paper investigates the relationship between supplier development and procurement performance in the public sector. Furthermore, the paper examines the moderating role of contract management difficulty on the relationship between supplier development and procurement performance. Using cross-sectional data collected from 179 public procuring entities, the main findings of the study are two-fold. Firstly, the relationship between supplier development and procurement performance in public sector is positive and significant (Ø~=~0.2343 and p =~0.0014). Also, contract management difficulty negatively and significantly moderates the relationship between supplier development and procurement performance (Ø~=~−0.1447 and p =~0.0190). In this aspect, the influence of supplier development on procurement performance is negatively affected by contract management difficulties. The study contributes to the supplier management, procurement performance, and contract management literature by providing empirical evidence on the role of supplier development on procurement performance in developing countries like Tanzania. Also, the conditional effects of contract management difficulty on the relationship between supplier development and procurement performance matter. The study's findings have important implications for procurement practitioners in the public sector and policy makers.
Keywords: 650; contract management difficulty; procurement; procurement performance; public procurement; supplier development; Suppliers